Pengaruh Konsorsium Mikroalga Tetraselmis sp. dan Chaetoceros sp. dengan Rasio N/P Terhadap Penurunan Nitrat dan Kelimpahan Mikroalga - Savira Fevilia; Okik Hendriyanto Cahyonugroho (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Microalgae are distributed in various types. Each type of microalgae has its own ability to absorb nutrients, especially nitrates. In several journals it is stated that microalgae are often used as phycoremediation. Nitrate and phosphate are macronutrients for microalgae that are needed based on certain ratios. So a lack of nitrogen content can result in substantial inhibition of algal growth and thus suboptimal nutrient consumption. This research aims to determine the effectiveness of microalgae consortia on nitrate removal and the effect of the N:P ratio on microalgae abundance. The microalgae used is Tetraselmis sp. and Chaetoceros sp. After being tested in batches, it was discovered that the Tetraselmis sp. consortium. and Chaetoceros sp. microalgae are able to remove nitrate content up to 94.1% with sample B1 (ratio of microalgae Chaetoceros sp. : Tetraselmis sp. = 100:0. This effectiveness occurs in the pH range 7.8 – 8.9 with a temperature of 28.67°C - 22, 67°C. The ratio of nitrate and phosphate content influences the abundance of microalgae. The ratio of 16:1 is influential in producing the highest abundance of more variations in microalgae consortia than other ratios.